2002
DOI: 10.1152/ajpgi.00031.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analysis of glutamine uptake in human hepatoma and liver-derived cells

Abstract: Inflammatory mediators including chemokines play a critical role in acute pancreatitis. The precise nature of early inflammatory signals within the pancreas remains, however, unclear. We examined the ability of isolated pancreatic acini to synthesize CC chemokine monocyte chemotactic protein-1 (MCP-1) and CXC chemokine cytokine-induced neutrophil chemoattractant (CINC) and the response to the secretagogue cerulein at physiological and supraphysiological concentrations. Isolated rat pancreatic acini maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
88
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 49 publications
8
88
0
Order By: Relevance
“…Analogous to our present observations, a neural amino acid transporter, ATB 0 , has also been shown previously to be overexpressed in cirrhotic liver samples (19). It has been further reported that the activity of ATA2 (20,21) is adaptively up-regulated in response to physiological changes such as nutrient starvation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analogous to our present observations, a neural amino acid transporter, ATB 0 , has also been shown previously to be overexpressed in cirrhotic liver samples (19). It has been further reported that the activity of ATA2 (20,21) is adaptively up-regulated in response to physiological changes such as nutrient starvation.…”
Section: Discussionsupporting
confidence: 91%
“…HCC cells may thus have compensatory mechanisms for specific amino acid uptake. In fact, it is known that a neutral amino acid transporter, ATB 0 is activated in HCC cells and promotes glutamine-dependent tumor growth (19).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the systemic glutamine homeostatic function of the liver is subverted, resulting in significantly decreased plasma glutamine levels in patients with liver cancer (16), an event that can adversely impact glutamine-dependent cells, such as those in the immune system (1). Previous work from our laboratory (6)(7)(8)(9) showed that human hepatoma cells take up glutamine at rates 10-to 30-fold faster than normal human hepatocytes via a transporter historically termed System ASC. This high-affinity Na ϩ -dependent glutamine transport activity is not expressed in normal hepatocytes (7).…”
mentioning
confidence: 99%
“…This transporter has also been identified as a cell surface receptor for mammalian retroviruses and is referred to as human ASCT2 (35). ATB 0 /ASCT2 expression was recently reported to be absent in normal human hepatocytes but present in six human hepatoma cell lines and primary liver tumors and shown to mediate the glutamine-dependent growth of rapidly growing human hepatoma cells (6). These results were confirmed by a recent query at the Cancer Genome Anatomy Project website (http://cgap.nci.nih.gov) that showed no ATB 0 / ASCT2 (accession #U53347) expression in normal human liver [0/34,164 expressed sequence tags (ESTs)] but appreciable expression in liver cancer (17/40,737 ESTs) using the Virtual Northern program.…”
mentioning
confidence: 99%
“…When amino acid is starved, the expression of ATA2 increases, suggesting that this expression is directly related to the activity of amino acid transporter [26] . Its mRNA increases in the biopsy of hepatocirrhosis and hepatic carcinoma [27] , especially in chorion after hepatectomy, suggesting that ATA2 is closely associated with hepatic regeneration [26,28] . ATA2 is cloned in hepatic carcinoma HepG2, and increases in patients of hepatic carcinoma [29] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%